Safety of anesthetic exposure on the developing brain - Do we have the answer yet? - Anju Gupta; Shruti Gairola; Nishkarsh Gupta (Wolters Kluwer Medknow Publications, 2020)
During the past two decades, a vast number of studies done on rodents and nonhuman primates have implicated general anesthetic exposure of developing brains in producing neurotoxicity leading to various structural and functional neurological abnormalities with cognitive and behavioral deficits later in life. However, it is still unclear whether these findings translate to children and whether single exposure to anesthesia in childhood can have long-term neuro-developmental risks. Considering the fact that a large number of healthy young children are undergoing elective surgery under general anesthesia globally, any such potential neurocognitive risk of pediatric anesthesia is a serious public health issue and is therefore important to understand. This review aims to assess the current preclinical and clinical evidence related to anesthetic neurotoxicity.